Principle of Freedom Contracts at a Company: Principio de libertad de contratación de una empresa - POHAN, M. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Employers’ and workers’ equality rarely meet for several reasons and realities. Equality between business owners’ and workers’ positions has also not been materialized if both parties do not have equal ability. This research used the normative juridical research method by inventorying the statutory regulations, especially in work agreements and the regulation of national legislation. Study’s results indicated that the first application of the freedom of contract principle in the work agreement has not been fully implemented because of the conditions of each different company. Secondly, the role of the government, business actors, and laborers/workers were not optimally been working. RESUMEN La igualdad de empleadores y trabajadores rara vez se cumple por varias razones y realidades. La igualdad entre los puestos de empresarios y trabajadores tampoco se materializa si ambas partes no tienen la misma capacidad. Esta investigación utilizó el método de investigación jurídica normativa mediante el inventario de las regulaciones estatutarias, especialmente en los convenios laborales y la regulación de la legislación nacional. Los resultados de este estudio indicaron que la primera aplicación del principio de libertad de contratación en el contrato de trabajo no se había implementado en su totalidad debido a las condiciones de cada empresa. En segundo lugar, el papel del gobierno, los actores empresariales y los obreros / trabajadores no funcionaba de manera óptima.